Management of use of urinary antimuscarinics and alpha blockers for benign prostatic hyperplasia in older adults at risk of falls: a clinical review - İlhan, Birkan; Erdoğan, Tuğba; Topinková, Eva; Bahat, Gülistan (European geriatric medicine, 2023)
PURPOSE: We aimed to outline the existing information and the underlying mechanisms of risk of falls associated with the use of urinary antimuscarinics for overactive bladder (OAB) or alpha-blockers for benign prostatic hyperplasia (BPH) in older adults. In addition, we aimed to provide assistance to clinicians in decision-making about (de-)prescribing these drugs in older adults. METHODOLOGY: Based on a literature search in PubMed and Google Scholar, we reviewed the literature, and identified additional relevant articles from reference lists, with an emphasis on the most commonly prescribed drugs in OAB and BPH in older patients. We discussed the use of bladder antimuscarinics and alpha-blockers, their potential side effects related to falls, and the deprescribing of these drugs in older adults. RESULTS: Urinary urgency or incontinence and lower urinary tract symptoms due to untreated OAB and BPH contribute to fall risk. On the other hand, the use of bladder antimuscarinics and alpha-blockers is also related to fall risk. They contribute to (or cause) falling through dizziness, somnolence, visual impairment, and orthostatic hypotension while they differ in their side-effect profiles regarding these problems. Falls are common and can cause a remarkable amount of morbidity and mortality. Thus, preventive measures should be taken to lower the risk. If the clinical condition allows, withdrawal of bladder antimuscarinics and alpha-blockers is recommended in fall-prone older adults. There are practical resources and algorithms that guide and assist clinicians in deprescribing these drug groups. CONCLUSIONS: The decision to prescribe or deprescribe these treatments in patients at high risk of falls should be individualized. In addition to explicit tools that are helpful for clinical decision-making in (de-)prescribing these drugs, STOPPFall (a recently developed expert-based decision aid specifically aiming to prevent falls) is present to assist prescribers in attaining decisions.
Keywords: alfa blokátory; hyperaktivní močový měchýř; Adrenergic alpha-Antagonists; Aged; Humans; mužské pohlaví; senioři; lidé; hyperplazie prostaty; úrazy pádem; Male; antagonisté muskarinových receptorů; Accidental Falls; Muscarinic Antagonists; symptomy dolních močových cest; Urinary Bladder, Overactive; Lower Urinary Tract Symptoms; Prostatic Hyperplasia